Analisis Kerentanan Dan Strategi Nafkah Rumah Tangga Petani Rawan Banjir di Desa Sindangmukti Kecamatan Kutawaluya Kabupaten Karawang - Hasna, Nadiyah; Azzahra, Fatimah; Budiandrian, Bayu (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2024)
The occurrence of vulnerability in farming households is influenced by many factors. One of the factors that occurred in Sindangmukti Village, Kutawaluya District, Karawang Regency was flooding conditions in rice fields. This flood occurred because water was sent from the river in Rengasdengklok District due to heavy rainfall so that the soil conditions could not seep water into the ground. The aim of this research is to analyze the vulnerability and livelihood strategies of rice commodity farmer households. This research uses the Sustainable Livelihood Approach (SLA) or sustainable livelihood approach in this research referring to the Department for International Development (DFID, 1999). The data collection technique used in this research is simple random sampling. Researchers used 57 respondents who own rice fields. The data analysis method used is a descriptive mixed method, namely quantitative and qualitative descriptive through in-depth interviews. The results of this research show that the livelihood vulnerability of Sindangmukti Village farmer households has very diverse capital or livelihood assets. This capital consists of human capital, natural capital, financial capital, physical capital and social capital. The calculation result of the Livelihood Vulnerability Index value in Sindangmukti Village is 0.441, which is included in the moderate or sufficient vulnerability category. Facing this situation, farmer households in Sindangmukti Village have to determine a livelihood strategy of intensificationin or extensification agricultural sector, pattern of living double, and spatial engineering (migration) in order to maintain and increase existing sources of income. Keywords: Farming households, livelihood strategies, LVI, vulnerability